2016
DOI: 10.1177/0192623315627216
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tumors in 26-Week Tg.Rash2 Mice Carcinogenicity Studies

Abstract: We report renal tubular adenomas and a carcinoma in 26-week Tg.rasH2 mouse carcinogenicity studies, which have not been reported to date either at our facility or in other published data. However, during the year 2014, renal tubular tumors were present in 4 studies conducted at our facility. Because of their morphological similarity to the amphophilic-vacuolar (AV) phenotypic variant of renal tubule tumors noted in Sprague-Dawley and Fischer 344 rats, which are thought to be familial, as well as the genetic ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Moreover, another study using acetone as one of the controls did not observe renal cell carcinoma in the acetone group after dermal application of acetone to rasH2 mice for 26 weeks (Urano et al 2007). Recently, Paranjpe et al (2016) reported that the development of renal cell tumors in rasH2 mice is random and spontaneous. Therefore, all neoplastic lesions observed in the male acetone group were considered spontaneous, and dermal applications of acetone in our 26-week carcinogenicity study using rasH2 mice did not exhibit carcinogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study using acetone as one of the controls did not observe renal cell carcinoma in the acetone group after dermal application of acetone to rasH2 mice for 26 weeks (Urano et al 2007). Recently, Paranjpe et al (2016) reported that the development of renal cell tumors in rasH2 mice is random and spontaneous. Therefore, all neoplastic lesions observed in the male acetone group were considered spontaneous, and dermal applications of acetone in our 26-week carcinogenicity study using rasH2 mice did not exhibit carcinogenic potential.…”
Section: Discussionmentioning
confidence: 99%